The Characteristic of Congenital Fetal Anomalies at Sanglah Birth Defect Integrated Center (SIDIC), Sanglah General Hospital, Bali Indonesia - Giri Chandra (Journal of Global Pharma Technology, 2020)
Introduction. Congenital anomalies are among the cause of neonatal morbidity and mortality. The aim of this study was to measure the occurrence of congenital fetal anomalies and explored the distribution of specific anomaly at SIDIC (Sanglah Birth Defect Integrated Center), Sanglah General Hospital Bali, Indonesia. Method. The study was a descriptive study of congenital anomalies who were screened at Maternal-Fetal Medicine Division outpatient clinic and who were delivered at Sanglah General Hospital Bali, Indonesia during the period January 2017-December 2018. Result. During two years study period, there were 109 pregnant women who gave birth to 118 babies with congenital anomalies. The system most involved were Gastrointestinal System 21.2% and Central Nervous System 21.2%. The majority of mother (70.6%) was at 20-35 years old. Regarding the gestational age, the majority accounting for 38.5% were at 28 - 34 weeks. Conclusion. In this descriptive study, the incidence of congenital anomalies most involving gastrointestinal system and Central Nervous system. Advanced in the knowledge of congenital anomalies could be important for better prevention. The preventive strategies such as preconception counselling, focused antenatal care, and care to optimized women’s health should be implemented. Keywords: Congenital anomalies, SIDIC, Fetal anomalies.